Health-related quality of life of postpartum women and associated factors in Dendi district, West Shoa Zone, Oromia Region, Ethiopia: a community-based cross-sectional study - Iranfachisa Gurmu Amana; Eden Girmaye Tefera; Eshetu Ejeta Chaka; Gizachew Abdissa Bulto (BMC, 2024)
Abstract Background Promoting a favorable experience of postpartum care has become increasingly emphasized over recent years. Despite the fact that maternal health care services have improved over the years, postnatal care service utilization is generally low and the health-related quality of life of postpartum women remains overlooked. Furthermore, the health-related quality of life of postpartum women is not well studied. Therefore, this study aimed to assess the health-related quality of life of postpartum women and associated factors in Dendi district, West Shoa Zone, Oromia, Region, Ethiopia. Methods A community-based cross-sectional study was conducted among 429 participants. A multistage stratified sampling procedure was used to select the sampling unit and simple random sampling technique was employed to select the study participants from 23 August 2022 to 16 November 2022. A pre-tested standard structured questionnaire was used to collect the data. Data were entered using Epi-Data 3.1 and then exported to Statistical package for social science version 26. Binary logistic regression analysis was computed at p-value < 0.25 were considered candidates for multivariable logistic regression. Adjusted Odds Ratios (AOR) with 95% confidence interval and statistical significance was declared at a p-value < 0.05. Results The study revealed that 73.7% (95% CI: 69.4-77.7) had a low level of health-related quality-of-life with a mean of 44.02 (SD ± 10.4). Urban residing [AOR = 0.27, 95% CI: (0.10-0.74)], no education [AOR = 3.44, 95% CI (1.35-8.74)], received at least four antenatal contact [AOR = 0.56, 95% CI (0.33-0.95)], received at least one postnatal care [AOR = 0.30, 95% CI (0.14-0.62)], poor social support [AOR = 2.23, 95% CI: (1.025-4.893)], having postpartum depression [AOR = 2.99, 95% CI: (1.52-5.56)], cesarean delivery [AOR = 3.18, 95% CI: (1.09-9.26)], and lowest household assets [AOR = 5.68, 95% CI: (2.74-11.76)] were significant associations with low health-related quality of life of postpartum women. Conclusions The health-related quality of life among postpartum women was very low. Postpartum women with low socio-economic status and inadequate maternal health service utilization had a low health-related quality of life. Promoting women's education and postnatal care services is needed to improve the health-related quality of life of postpartum women.